2021
DOI: 10.1021/acs.est.1c04453
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical Aging of Atmospheric Fine Particles as a Potential Source for Gas-Phase Hydrogen Peroxide

Abstract: Atmospheric hydrogen peroxide (H2O2), as an important oxidant, plays a key role in atmospheric sulfate formation, affecting the global radiation budget and causing acid rain deposition. The disproportionation reactions of hydroperoxyl radicals (HO2) in both gas and aqueous phases have long been considered as dominant sources for atmospheric H2O2. However, these known sources cannot explain the significant formation of H2O2 in polluted areas under the conditions of high NO levels and low ambient relative humidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…This could be explained by the unknown sources of gaseous H 2 O 2 during haze events that have not been considered in this model. Recent studies have found that photooxidation processes involving organics can release H 2 O 2 , , accounting for the “missing” sources of gas-phase H 2 O 2 . Furthermore, the net photoreaction effects on the H 2 O 2 budget should also be considered in future models.…”
Section: Results and Discussionmentioning
confidence: 99%
“…This could be explained by the unknown sources of gaseous H 2 O 2 during haze events that have not been considered in this model. Recent studies have found that photooxidation processes involving organics can release H 2 O 2 , , accounting for the “missing” sources of gas-phase H 2 O 2 . Furthermore, the net photoreaction effects on the H 2 O 2 budget should also be considered in future models.…”
Section: Results and Discussionmentioning
confidence: 99%
“…20,21 The photochemical aging of atmospheric fine particles can directly produce abundant gas-phase H 2 O 2 by a reaction between the particle surface −OH groups and HO 2 • radicals formed by photooxidation of chromophoric dissolved organic matter (CDOM). 22 Moreover, brown carbon (BrC) induced HO 2…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies found that ammonium sulfate seeds containing glyoxal exposed to UV light and organic precursors (e.g., limonene, isoprene, α-pinene, β-pinene, and toluene) exhibited a photoinduced SOA growth . Further studies have shown that this may be attributed to the formed photosensitizers, which can initiate radical chemistry and contribute to additional aerosol aging. , The photochemical aging of atmospheric fine particles can directly produce abundant gas-phase H 2 O 2 by a reaction between the particle surface −OH groups and HO 2 • radicals formed by photooxidation of chromophoric dissolved organic matter (CDOM) . Moreover, brown carbon (BrC) induced HO 2 • and organic radicals with an upper limit of 20 and 200 M/day .…”
Section: Introductionmentioning
confidence: 99%
“…Hydroxyl radicals (·OH) are highly reactive species that are found throughout nature and are involved in a wide range of important chemical reactions. , In the atmosphere, ·OH is responsible for driving the rapid conversion of gaseous pollutants, such as volatile organic compounds (VOCs) and nitrogen oxides (NO x ), into secondary organic aerosols (SOAs) and nitrate. These chemical reactions are crucial in the formation and growth of fine particles during haze events, which can have severe environmental and health impacts. Additionally, ·OH plays an essential role in the oxidation of sulfur dioxide (SO 2 ) into sulfate and the deposition of acid rain, which can harm aquatic and terrestrial ecosystems. , In aquatic systems, ·OH is a crucial player in accelerating the cyclings of elements, such as the oxidation and mineralization of organic carbon. , ·OH is also involved in the transformation of pollutants, such as pesticides, pharmaceuticals, and other organic contaminants. , Understanding the role of ·OH in these processes is vital for predicting and mitigating the impacts of environmental pollution on human and ecosystem health.…”
Section: Introductionmentioning
confidence: 99%
“…3−5 Additionally, •OH plays an essential role in the oxidation of sulfur dioxide (SO 2 ) into sulfate and the deposition of acid rain, which can harm aquatic and terrestrial ecosystems. 6,7 In aquatic systems, •OH is a crucial player in accelerating the cyclings of elements, such as the oxidation and mineralization of organic carbon. 8,9 •OH is also involved in the transformation of pollutants, such as pesticides, pharmaceuticals, and other organic contaminants.…”
Section: ■ Introductionmentioning
confidence: 99%